A REVIEW: THERAPEUTIC, MEDICINAL AND FOOD USES OF ALOE VERA - Ahmed, Fatma A; El-Bassossy, Taha AI; Abdelgawad, Ahmed AM (Universal Journal of Pharmaceutical Research, 2024)
The history for the use of Aloe vera for medicinal purposes starts from about 3000 years. Medicinally, this plant may be able to treat skin cancer as well as sunburns, burns, and small wounds. More than 104 compounds from various parts of this plant, including minerals, vitamins, amino acids, enzymes, sterols, anthraquinone, flavonoids, terpenoids, coumarins, polysaccharides, sugars, and polyphenols, have been isolated thus far, according to scientific reports on phytochemical analysis of this plant. The biological activities of these compounds are diverse and include anthelmintic, hepatoprotective, antidiabetic, diuretic, antibacterial, antiviral, antioxidant, antiseptic, anti-inflammatory, anticancer, and cosmetic effects for medical therapy. This article mainly emphasizes therapeutic, medicinal and food uses of A. vera. Peer Review History: Received: 3 October 2023; Revised: 9 November; Accepted: 26 December; Available online: 15 January 2024 Academic Editor: Dr. Tamer Elhabibi , Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Reviewers: Ahmad Najib, Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Prof. Ali Gamal Ahmed Al-kaf, Sana'a university, Yemen, alialkaf21@gmail.com